2000
DOI: 10.1002/(sici)1097-0339(200002)22:2<136::aid-dc19>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic spindle-cell squamous carcinoma arising in association with tall-cell papillary cancer of the thyroid: A potential pitfall

Abstract: The following is a correction to the original article that appeared in Diagnostic Cytopathology 1999;21:413–418. Owing to a publisher's error, Figure 4C on p. 415 was incorrectly reproduced. The correct illustrations and captions for this page are given here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…2 3 This transformation is rare and usually confers a poor prognosis, and despite current therapeutic methods the survival rate is very low. [2][3][4][5][6] This particular case report describes the histological and immunohistochemical findings of this rare transformation of papillary tall cell carcinoma of the thyroid into moderately to poorly differentiated squamous cell carcinoma. Take home messages N We describe a rare case of transformation of papillary tall cell carcinoma of the thyroid into moderately to poorly differentiated squamous cell carcinoma N Histology of the subsequent total thyroidectomy specimen revealed a biphasic tumour comprising areas of tall cell papillary carcinoma merging with moderately to poorly differentiated squamous cell carcinoma N Such a transformation is rare and usually confers a poor prognosis…”
Section: Discussionmentioning
confidence: 99%
“…2 3 This transformation is rare and usually confers a poor prognosis, and despite current therapeutic methods the survival rate is very low. [2][3][4][5][6] This particular case report describes the histological and immunohistochemical findings of this rare transformation of papillary tall cell carcinoma of the thyroid into moderately to poorly differentiated squamous cell carcinoma. Take home messages N We describe a rare case of transformation of papillary tall cell carcinoma of the thyroid into moderately to poorly differentiated squamous cell carcinoma N Histology of the subsequent total thyroidectomy specimen revealed a biphasic tumour comprising areas of tall cell papillary carcinoma merging with moderately to poorly differentiated squamous cell carcinoma N Such a transformation is rare and usually confers a poor prognosis…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of the TP53 gene has been reported to be present in both tall cell73 and insular74 thyroid tumors. As well, both of these variants have been reported in association with anaplastic tumors 18, 23, 28, 32, 33. Whether the biologically aggressive tall cell and insular subtypes of papillary carcinoma arise as a consequence of the early genetic events involved in anaplastic transformation, or whether they represent side branches of this evolutionary process, currently is unknown.…”
Section: Molecular Evidencementioning
confidence: 91%
“…In a study analyzing entire organ sections, Ibanez et al24 found all anaplastic tumors studied to contain foci of DTC. It is also interesting to note that biologically aggressive histologic subtypes of papillary carcinoma, which include insular and tall cell types, have been found in association with anaplastic tumors 18, 23, 28, 32, 33. This finding has led some authors to hypothesize that these differentiated subtypes represent intermediate forms in the anaplastic transformation process 18, 23, 28, 32, 33…”
Section: Pathologic Evidencementioning
confidence: 99%
“…Anaplastic thyroid carcinoma (ATC) is recognized as one of the most aggressive primary thyroid malignancies . ATC accounts for less than 5% of thyroid cancers, with a peak incidence in the 6th to 7th decades . The majority of cases are fatal, often between 6 months and 1 year after presentation, with a median 1‐year survival rate of only 10% to 20%.…”
Section: Anaplastic Thyroid Carcinomamentioning
confidence: 99%